Prevalence and Outcome of Serum Autoantibodies in Chronic Hepatitis C Patients Undergoing Direct-Acting Antiviral Treatment - Romano, Ciro; Tortorella, Olga; Dalla Mora, Liliana; Di Stasio, Dario; Sellitto, Ausilia; Adinolfi, Luigi Elio; Marrone, Aldo (Frontiers in Immunology, 2022)
Background: Chronic immune stimulation by hepatitis C virus (HCV) may cause occurrence of several autoantibodies in infected patients, with or without features of clinically overt autoimmune diseases. The recent introduction of direct-acting antivirals (DAAs) has dramatically changed the natural history of chronic HCV infection. The aim of this study was to assess the effects of DAA therapy on serum autoantibodies in chronic hepatitis C (CHC) patients. Methods: The medical records of 113 CHC patients were reviewed to assess autoantibody behavior following DAA-directed HCV eradication. Statistical analysis was performed to assess correlations between DAA treatment and autoantibody titers, HCV genotypes, and viral loads. Results: Anti-nuclear (ANA), anti-smooth muscle cell (ASMA) and anti-mitochondrial (AMA) antibody testing was available in 77 patients; 31 out of 77 patients (40%) had one or more serum autoantibodies prior to treatment. Measurement of autoantibody titers before and after HCV eradication was performed in 20 of 31 patients. DAA treatment significantly affected ANA and ASMA titers, leading to disappearance or reduction of autoantibody titers; conversely, AMA were not influenced by DAA treatment. No correlations were observed between autoantibody specificity and both HCV genotypes and viral loads at baseline. Likewise, serum autoantibody titers were independent of HCV genotypes. Conclusions: DAA-directed HCV clearance may interrupt chronic immune stimulation by removing the drive for autoantibody induction. The isolated persistence of autoantibodies in the small fraction of patients who did not show clearance following DAA treatment may require long-term vigilance.